Inhibition of CD147 expression by RNA interference reduces proliferation, invasion and increases chemosensitivity in cancer stem cell-like HT-29 cells - CHEN, JIE; PAN, YUQIN; HE, BANGSHUN; YING, HOUQUN; WANG, FENG; SUN, HUILING; DENG, QIWEN; LIU, XIAN; LIN, KANG; PENG, HONGXIN; CHO, WILLIAM C; WANG, SHUKUI (International journal of oncology, 2015)
The association between CD147 and cancer stem cells (CSCs) provides a new angle for cancer treatments. The aim of this study was to investigate the biological roles of CD147 in colorectal CSCs. The Oct4-green fluorescent protein (GFP) vector was used to isolate CSCs and pYr-mir30-shRNA was used to generate short hairpin RNA (shRNA) specifically for CD147. After RNA interference (RNAi), CD147 was evaluated by reverse transcription-quantitative PCR and western blot analysis, and its biological functions were assessed by MTT and invasion assays. The results showed that the differentiation of isolated CSC-like HT-29 cells was blocked and these cells were highly positive for CD44 and CD147. RNAi-mediated CD147 silencing reduced the expression of CD147 at both mRNA and protein levels. Moreover, the activities of proliferation and invasion were decreased obviously in CSCs. Knockdown of CD147 increased the chemosensitivity of CSC-like cells to gemcitabine, cisplatin, docetaxel at 0.1, 1 and 10 μM respectively, however, there was no significant difference among the three groups to paclitaxel at 10 μM. In conclusion, these results suggest that CD147 plays an important role in colorectal CSCs and might be regarded as a novel CSC-specific targeted strategy against colorectal cancer.